MITIGASI KAMPANYE HOAKS DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR 2024 DI BAWASLU PROVINSI JAWA BARAT - Annisa (Jurnal Keadilan Pemilu, 2024)
The Provincial Election Supervisory Agency (Bawaslu) of West Java is one of the institutions responsible for overseeing the Governor and Deputy Governor elections in West Java Province. According to the Election Vulnerability Index for West Java Province, which is at a high-risk level (level four), particularly in the subdimension of candidate campaigns, there is a risk of the spread of hoax materials on social media during the campaign phase. Therefore, this study aims to analyze the mitigation measures taken by Bawaslu West Java to address the spread of hoaxes in campaigns. In this regard, Mintzberg’s institutional roles theory is used as the theoretical framework to analyze Bawaslu’s role in supervising the regional head election process. The research method employed is a descriptive method with a qualitative approach. The results indicate that Bawaslu West Java has successfully mitigated hoax campaigns, as evidenced by the resolution of 31 hoax campaign cases.